Analysis of Curriculum Policy Development and Implementation of Independent Curriculum in Elementary Schools - Fitriyani, Fitriyani; Kurnia, Ira Restu; Fadillah, Siska Nur; Oktaviani, Anna Maria (CV. Pusdikra Mitra Jaya, 2023)
This research is to find out and examine the